Exploring Tourism Entrepreneurial Resilience for Minangkabau Women in the Disaster Preparedness - Zahra, Aini; Sari Lenggogeni; Vera Pujani (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This paper explores the resilience of Minangkabau women tourism entrepreneurs in facing disasters, identifies the factors that support their resilience, and the strategies used in disaster preparedness. The research method used is a qualitative approach with in-depth interviews and case studies of female tourism entrepreneurs in disaster-affected areas. The research method used is a qualitative approach with in-depth interviews and case studies of women tourism entrepreneurs in disaster-affected areas. The number of informants interviewed was 15 women entrepreneurs spread across West Sumatra, namely Solok, Padang, Padang Panjang, Bukittinggi, and Pesisir Selatan. The research results show that Minangkabau cultural values, such as the spirit of cooperation and the role of women in the family economy, are the main factors in their resilience. In addition, innovation in business, the use of digital technology, and community support contribute to the sustainability of their enterprises. This study emphasizes the importance of disaster preparedness in tourism business strategies and provides recommendations to enhance the resilience of women entrepreneurs in disaster-prone areas.